2005
DOI: 10.1196/annals.1360.015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Music Training on the Child's Brain and Cognitive Development

Abstract: Research has revealed structural and functional differences in the brains of adult instrumental musicians compared to those of matched nonmusician controls, with intensity/duration of instrumental training and practice being important predictors of these differences. Nevertheless, the differential contributions of nature and nurture to these differences are not yet clear. The musician-nonmusician comparison is an ideal model for examining whether and, if so, where such functional and structural brain plasticit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
246
0
19

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 357 publications
(276 citation statements)
references
References 31 publications
11
246
0
19
Order By: Relevance
“…Orchestral musicians and controls, matched for handedness, age, and verbal intelligence, demonstrated a neural and behavioral dissociation on verbal and visuospatial tasks in that there were no differences in either behavioral data or Broca's area activation during performance of the verbal task, but there were significant differences, both behaviorally and neurofunctionally, during the visuospatial task performance. Our findings extend the current and growing literature reporting the transferable benefits of music performance training to nonmusical cognitive abilities in children and adolescents (Costa-Giomi, 2004;Schellenberg, 2004Schellenberg, , 2005Schellenberg, , 2006Schlaug et al, 2005). Indeed, these findings have important implications, by providing additional objective evidence to support the suggestion that the development and maintenance of musical performance abilities confers benefit to nonmusical cognitive domains.…”
Section: Discussionsupporting
confidence: 73%
“…Orchestral musicians and controls, matched for handedness, age, and verbal intelligence, demonstrated a neural and behavioral dissociation on verbal and visuospatial tasks in that there were no differences in either behavioral data or Broca's area activation during performance of the verbal task, but there were significant differences, both behaviorally and neurofunctionally, during the visuospatial task performance. Our findings extend the current and growing literature reporting the transferable benefits of music performance training to nonmusical cognitive abilities in children and adolescents (Costa-Giomi, 2004;Schellenberg, 2004Schellenberg, , 2005Schellenberg, , 2006Schlaug et al, 2005). Indeed, these findings have important implications, by providing additional objective evidence to support the suggestion that the development and maintenance of musical performance abilities confers benefit to nonmusical cognitive domains.…”
Section: Discussionsupporting
confidence: 73%
“…Numerous other studies have shown similar effects of musical training on brain structure (Bermudez & Zatorre, 2005;Oechslin, Van de Ville, Lazeyras, Hauert, & James, 2013;Schlaug, Jänke, Huang, Staiger, & Steinmetz, 1995;Schlaug, Norton, Overy, & Winner, 2005;Schmithorst & Wilke, 2002), suggesting the possibility that musicians and non-musicians reacted to the stimuli in the current experiment in different ways.…”
Section: Effects Of Musical Abilitymentioning
confidence: 71%
“…Interestingly, structural differences in the primary motor cortex between keyboard and string instrument players have been reported (Schlaug et al, 2005). The majority of the keyboard players had an elaborated configuration of the precentral gyrus on both sides, whereas most of the adult string players had this atypicality only in the right hemisphere.…”
mentioning
confidence: 99%